Strategi Penghimpunan Dana ZIS di Masa Pandemi Covid-19 (Studi Kasus LAZ Nahwa Nur) - Firda Ahyani; Fahmi Syahbudin (Neolectura, 2020)
The Covid-19 pandemic that originated in Wuhan China attacked Indonesia in March 2020. There are so many impacts as a result of it, one of which is national health that has resulted in an economic problem. In the midst of this pandemic, it turns out that the collection of Amil Zakat Institutions has increased, one of which is LAZ Nahwa Nur which has increased by 400%. This research is a qualitative research using descriptive method. Data obtained by means of observation, interviews and documentation. Then the data was processed using the Miles and Hubermen method. The results of the research show that the Nahwa Nur Amil Zakat Institute focuses on collection activities with direct and indirect fundraising strategies with high enthusiasm inviting people to give zakat, donations and alms / donate in the midst of the Covid-19 pandemic situation. Direct strategies include zakat pick-up and zakat counter services, while indirect strategies include Web-based digital fundraising, crowd funding, and program campaigns through Facebook and ig. The main strategies carried out by the LAZ Nahwa Nur are web-based digital fundraising strategies, crowd funding, Facebook, and Instagram.